Avaliação da cultura de segurança do paciente na prática clínica do centro odontológico do hospital da polícia civil de Minas Gerais em Belo Horizonte - Camilla Rossi Peracio (2024)
The expansion of access to health services, the dissemination of information and technological advances have resulted in important transformations for modern health care systems, making concern for patient safety a priority and encouraging the improvement of care processes. Safety culture encompasses actions, skills and behaviors that directly impact the quality of care at different levels and reinforces the importance of evaluating the culture and safety climate of a healthcare institution. There is a gap in the literature regarding studies on patient safety in dentistry and primary health care. In this context, the study aimed to assess knowledge of safety culture and patient safety by the multidisciplinary team at the Dental Center of the hospital of the Polícia Civil de Minas Gerais. Furthermore, the influence of safety culture on the effectiveness of actions and notifications of adverse events was analyzed. A cross-sectional observational study was developed. Data collection was carried out using the Hospital Survey on Patient Safety Culture 1.0 Brazilian version questionnaire, distributed to 61 employees of the institution. Data were analyzed using the Statistical Package for the Social Sciences 21.0 software. The study was approved by the research ethics committee of the Universidade Federal de Minas Gerais under protocol nº 6.471.369 and CAAE: 74484423.0.0000.5149. The response rate was 85.24% (n=52). The patient safety rating was considered very good by 47.5% (n=29) of respondents. 61.5% (n=32) agreed that the team supports each other, 54.9% (n=28) that people treat each other with respect, 67.3% (n=35) that the supervisor pays attention to problems of patient safety, 58.8% (n=30) have the freedom to speak out when observing situations that may affect care. 50% (n=26) considered that their mistakes could be used against them, 36.7% (n=18) that the focus of the error fell on the person and not on the problem and 44% (n=22) were worried errors are recorded on the functional sheets. The vast majority of respondents, 90.4%, did not report any adverse events in the last 12 months (n=47). Data analysis allowed the delineation of the safety climate and patient safety in the institution in addition to the identification of structural, behavioral and routine problems. Thus, enabling the establishment of strategies to implementation of a safety culture program, standardization of work routines, ongoing team education in addition to the evaluation and monitoring of work processes, with the aim of mitigating damage and offering safe patient-centered healthcare.